Rational Design of the Cyclically Symmetrical Structure - Misura, Serhii; Smetankina, Natalia; Misiura, Ievgeniia (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2020)
The problem of optimal design of a Kaplan turbine cover operating in the normal mode is solved. The geometric parameters of the cover are modified to minimize the cover weight. To calculate the parameters of the strainstress state, the finite element method is used. Optimization was performed using the gradient method. The design variables are the thicknesses of structural elements. The weight of the cover was reduced by 30 %, and the rolled stock thickness range was downsized by five positions. In this case, the stress values in the optimal structure did not exceed admissible ones.
Keywords: optimization; Kaplan turbine; strain-stress state; gradient method; finite element method